New method to assess the air permeance into vacuum insulation panel. (February 2018) - Yrieix, Bernard; Pons, Emmanuelle
Graphical abstract: Highlights: A new simple method for assessment of air permeation into vacuum insulation panels. Total internal pressure measurements at low temperature give air pressure. The method is valuable on VIP from the laboratory as well as from the field. It allows also at the same time the determination of water vapour permeation. The method is not very convenient for fibreglass cores but is accurate on silica cores.